Online Pathways, Digital Migrant workers: From Empowerment to Monitor Digital Footprints for Refugees - Rajan Fletcher (International Journal of Science and Society, 2021)
The text studies how digitality and refugee routes intersect by focussing on the concepts of »connected migrants and the digital footprints of refugee routes in transnational spaces. The smartphone is a key signifier of today’s refugee, and possession of one is questioned by government policies of legitimisation and public opinion perceptions of what constitutes a genuine refugee. These overlook the complex question of digital rights and migration’s embeddedness in the fluidity of the postmodern world. The text thus deals with the digital world’s ambivalence, which is not just a one-way relation of empowerment but entails the risk of complete control over a refugee’s body as well. We establish that an important shift has occurred in European policies, one most visible in the process of erasing the electronic traces of refugees on the move and the illegal return of refugees to the previous country on their way, the socalled pushbacks.